2020
DOI: 10.3389/fonc.2020.01400
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Prognostic Role of PD-L1 in Upper Tract Urothelial Carcinoma Patients Underwent Radical Nephroureterectomy: A Systematic Review and Meta-Analysis

Abstract: Background: Several studies investigating the role of PD-L1 in upper tract urothelial carcinoma (UTUC) patients after radical nephroureterectomy (RNU) to predict prognosis had been published and great controversy existed among them. We, therefore, in the meta-analysis, reported the association between PD-L1 and survival in UTUC patients who underwent RNU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…Positive PD-L1 was observed in 7 (16.3%) patients with a cut-off value of 5% and better PFS was observed in patients with positive PD-L1. Some studies have reported that overexpression of PD-L1 adversely affects survival [21]. Conversely, other studies have reported that positive PD-L1 was related with radiosensitivity in various tumors [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive PD-L1 was observed in 7 (16.3%) patients with a cut-off value of 5% and better PFS was observed in patients with positive PD-L1. Some studies have reported that overexpression of PD-L1 adversely affects survival [21]. Conversely, other studies have reported that positive PD-L1 was related with radiosensitivity in various tumors [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic predictive value of PD-L1 in UTUC is controversial [21]. The cut-off level of PD-L1 varies between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, correlations were observed between PD-L1 positivity on tumoral cells and the worse outcomes in UTUC patients, although PD-L1 expression rate varied between 20−25% depending on the study and the cutoff used [41,42].…”
Section: The Immune Microenvironment Of Utucmentioning
confidence: 94%
“…advanced and unresectable or metastatic UC demonstrated encouraging results in response rate and toxic effect (14,15). The incidence rate of PD-L1 expression in UTUC patients was approximately 13.0-30.0% and PD-L1 overexpression related to a more aggressive nature (16) and shorter OS in UTUC patients after RNU (17). However, the relationship between PD-L1 expression and response to therapy with PD-L1 inhibitors remains unclear.…”
Section: E Fmentioning
confidence: 99%